2018
DOI: 10.1557/jmr.2018.419
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability study of transition metal perovskite sulfides

Abstract: Transition metal perovskite chalcogenides, a class of materials with rich tunability in functionalities, are gaining increased attention as candidate materials for renewable energy applications. Perovskite oxides are considered excellent n-type thermoelectric materials.Compared to oxide counterparts, we expect the chalcogenides to possess more favorable thermoelectric properties such as lower lattice thermal conductivity and smaller band gap, making them promising material candidates for high temperature therm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 40 publications
5
84
0
Order By: Relevance
“…The band gap energies of αand β-SrZrS 3 are predicted at 1.38, and 1.95 eV, respectively. The predicted values are in close agreement with the estimated optical band gaps from diffuse-reflectance measurements: α-SrZrS 3 (1.52 eV) and β-SrZrS 3 (2.05 eV) [16]. It is evident from the projected density of states (Figure 5a,b) that the conduction band edge, in both phases, is dominated by Zr-d states.…”
Section: Electronic Propertiessupporting
confidence: 84%
See 4 more Smart Citations
“…The band gap energies of αand β-SrZrS 3 are predicted at 1.38, and 1.95 eV, respectively. The predicted values are in close agreement with the estimated optical band gaps from diffuse-reflectance measurements: α-SrZrS 3 (1.52 eV) and β-SrZrS 3 (2.05 eV) [16]. It is evident from the projected density of states (Figure 5a,b) that the conduction band edge, in both phases, is dominated by Zr-d states.…”
Section: Electronic Propertiessupporting
confidence: 84%
“…We can see that clear differences between the assigned peaks of α-SrZrS 3 and β-SrZrS 3 , which is consistent with the difference in their lattice parameters. All the peaks in the simulated DFT spectrum match very closely with the experimental XRD measurement from the work of Niu et al [34], as shown (Figure 2b). We consider that the assigned reflection peaks in the DFT XRD spectrum may become useful in clarifying future experiments, for instance to distinguish between the α-SrZrS 3 and β-SrZrS 3 phases.…”
Section: Structural Propertiessupporting
confidence: 83%
See 3 more Smart Citations